2005
DOI: 10.1007/s00066-005-1358-y
|View full text |Cite
|
Sign up to set email alerts
|

Selective Radioprotection of Normal Tissues by Bowman-Birk Proteinase Inhibitor (BBI) in Mice

Abstract: BBI acts as a potent selective normal-tissue radioprotector in vitro and in vivo, apparently without protecting tumors, and thus has the potential to improve clinical radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…BBI is a well-characterized soy protein (6) that has anticarcinogenic (41), chemoprotective (19), and radioprotective (10,15) effects via mechanisms of action that include serine protease inhibition (6) and antioxidant properties (14,15,39). In support of the latter mechanism, BBI has been shown to lessen production of reactive oxygen species by nonmuscle cell types (14,39) and to diminish the systemic oxidative stress caused by whole body irradiation (15).…”
mentioning
confidence: 99%
“…BBI is a well-characterized soy protein (6) that has anticarcinogenic (41), chemoprotective (19), and radioprotective (10,15) effects via mechanisms of action that include serine protease inhibition (6) and antioxidant properties (14,15,39). In support of the latter mechanism, BBI has been shown to lessen production of reactive oxygen species by nonmuscle cell types (14,39) and to diminish the systemic oxidative stress caused by whole body irradiation (15).…”
mentioning
confidence: 99%
“…The radioprotective properties of BBI have been tested on cell cultures; so far, no data regarding efficacy in humans are available. Soybean BBI have shown potent and selective radioprotection of normal tissue in vitro [80] and in vivo [81], without protecting tumor tissue. Dittmann et al [81] showed that soybean BBI increased clonogenic survival after irradiation only in cells, either normal or transformed, having a wild-type p53 tumor suppressor gene.…”
Section: Radioprotectionmentioning
confidence: 99%
“…Soybean BBI have shown potent and selective radioprotection of normal tissue in vitro [80] and in vivo [81], without protecting tumor tissue. Dittmann et al [81] showed that soybean BBI increased clonogenic survival after irradiation only in cells, either normal or transformed, having a wild-type p53 tumor suppressor gene. In a cell line with inducible expression of mutated p53, the radioprotective effect of BBI was only detected when the expression of the mutated p53 was switched off [75].…”
Section: Radioprotectionmentioning
confidence: 99%
“…It was demonstrated that pretreatment of mice with BBI significantly decreased radiationinduced leg contracture 47 . Based on the previous experiments, it was determined that this inhibitor improved DNA repair of initial damage and thus enhanced genomic integrity and prevented radiation-induced terminal differentiation of fibroblasts 46 .…”
Section: Modifiers Of Cell Signallingmentioning
confidence: 99%